Application of Quality Function Deployment for Design and Development of Artificial Muscle Fabrication Device - Addis, Birhanu (CMBES Proceedings, 2024)
The field of artificial muscles has garnered significant attention due to their suitability for biomedical and robotic applications. Particularly, twisted, and coiled nylon fiber actuators, a type of artificial muscle, exhibit significant potential. However, the current manufacturing process for these actuators often lacks consistency and repeatability. Moreover, existing fabrication devices demonstrate a marked limitation, specifically, their capacity to generate only a single kind of artificial muscle. This study proposes the application of the Quality Function Deployment framework to design and develop a reliable machine for fabricating twisted and coiled artificial muscle. An array of customer requirements was obtained from literature and surveys, and these were prioritized and translated into product specifications via the QFD tool. The proposed design addresses several key requirements, including the capability to fabricate distinct types of artificial muscles, automated operation, and improved product uniformity. The implementation of QFD offers a structured and customer-focused approach that helps in concept design generation by considering the priority of customers and the importance of technical specifications. Future studies are recommended to validate the proposed design with prototyping and testing.